Culturas infantis: crianças plurais, plural da infância no cotidiano da educação infantil - Campos, Gleisy Vieira (2013)
This research aimed to investigate and understand the social condition of childhood and identity construction through cultural productions of young children in peer relations in spacetime recess, in collective activities, free and directed, and festivities held in Early Childhood Center Itabuna -BA. The central concern in this research refers to the need to expand the concept of childhood beyond the theoretical conceptions developmental, but to put them in perspective, recognizing its possibilities and limitations. Accordingly, in addition to an age range, develop a study in space and time focusing on routine, from an ethnographic perspective and through participant observation, collective experience among children of the same age and of different ages in moments of recreation, hospitality and festivities. The observations of the children\'s activities were recorded in photos, videos and field notes; Interviews were conducted with twenty-five infants between 3 and 5 years, eight teachers of the institution and four professional management team - principal, assistant principal and two pedagogical coordinators. This research was based on the sociology of childhood and the studies that have been conducted in the field on childhood cultures, with the core concept of childhood as a social construction and children as social actors, active subjects in the conduct of their lives and the construction of society in which they operate. In this way, the partnership with children from CEMEI and their voices guided us during the development of the field work and also guided in the analysis and interpretation presented. Our analysis confirms that children contradict the universal and naturalized concepts of childhood presented by the teachers, because they present themselves as cultural subjects, social actors that in the relations established between them, with adults and with institutional order they constitute their cultures. Thus, the ways of formation and organization of groups, the relationships of friendship, the strategies of participation in child\'s play, the conflicts resolutions, the construction of joint and coordinated actions and the relations with school rules are analyzed as structural elements of children\'s culture.